Exploring Digital Flashcards for Enhancing English Vocabulary Learning in Elementary Students - Suwandi, Suwandi (Proceeding International Conference on Religion, Science and Education, 2024)
This research examined EFL elementary school students' purposeful vocabulary acquisition using a digital flashcard tool in self-study. This research used Quizlet as a Computer Assisted Vocabulary Learning (CAVL) tool to have students repeat an intentional vocabulary learning activity at home for four weeks. This research included weekly vocabulary learning records, assessments, questionnaires, and individual interviews. Content and statistical analysis were used to examine the data. Students who used Quizlet more often gained more vocabulary, and there was a substantial association between digital flashcard usage and vocabulary increases. The students also liked utilizing digital flashcards for self-study, and Quizlet's features, convenience of use, and language learning potential were their main perks. This study's results help language instructors understand EFL students' deliberate vocabulary acquisition using the suggested digital flashcard technology.